PARTISIPASI TOKOH MASYARAKAT DALAM TOLERANSI UMAT BERAGAMA - Muzaki, Muzaki (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2010)
The need for efforts to build harmony among religious believers in Indonesia recently has increased significantly.This can be seen from the rampant activities of interreligious dialogue in the regions. Strategic step for the future is to buildmutual understanding, cooperation, and appreciates between religion’s adherents. To build a harmonious religioustolerance was necessary active role of all elements of the nation regardless of their beliefs, not to mention his owninvolvement in a means that allows for participation, such as with an active role through the Political Parties (Party), NonGovernmental Organizations (NGOs) or mass organizations and other social activities.